The Environmental Commons in Urban Communities: The Potential of Place-Based Education - Flanagan, Constance; Gallay, Erin; Pykett, Alisa; Smallwood, Morgan (Frontiers in Psychology, 2019)
The reflections of 205 4-12th graders (most from racial/ethnic minority backgrounds) on what they learned from participating in place-based stewardship education (PBSE) projects in their urban communities were analyzed. All projects involved hands-on collective learning/action by teams of students, teachers, and community partners in the communities where they attended school. Reflections were analyzed using an iterative process of deductive and inductive coding and identifying emergent themes. Deductive coding was informed by the authors’ earlier theoretical and empirical work on the environmental commons (EC) and the key principles outlined in Elinor Ostrom’s work on effective group practices for stewarding common pool resources. Reflections were coded for up to 8 discrete references to the two elements of the environmental commons: 1) the natural resources on which life depends (awareness of nature in the urban space; nature’s diversity and ecological balance; interdependence of humans with nature; healthy environments and species’ well-being, students’ environmental identities; and human impact and agency); and 2) collective actions to protect a community’s resources (benefits and responsibilities of team work, within-group dynamics and civic skills, collective efficacy, generativity, and identification with the broader community). We found that students articulated, with varying levels of understanding, the two key EC elements. Most referred to positive human impact and a third mentioned negative human impact. When discussing the community benefitting from their work, a majority mentioned humans; yet nearly half referred to other species or living systems; and a quarter referenced generativity, the legacy of their work for the future. Concerning the collective orientation of projects: one-third felt collective action was imperative for solving environmental issues, half expressed feelings of collective efficacy. And over one-third referenced their increased attachment and identification with a broader community (school, city, or nature). Core practices in this PBSE model parallel the elements of effective groups identified by Ostrom. We conclude with a discussion of the potential of PBSE projects in urban communities for developing young people’s sense of the public realm more broadly and their stake in the natural environment and their communities.